2000
DOI: 10.1177/09680519000060040701
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial endotoxin (lipopolysaccharide) stimulates the rate of iron oxidation

Abstract: Bacterial endotoxin (lipopolysaccharide) has affinity for a number of cations, including iron. Previous investigations have demonstrated that lipopolysaccharide can affect the oxidation rate of iron; heme-bound ferrous iron in hemoglobin is oxidized to ferric iron when hemoglobin binds lipopolysaccharide. In the present study, we directly examined the interaction between lipopolysaccharide and iron. Lipopolysaccharide caused a concentration-dependent increase in the rate of iron oxidation, with up to a 23-fold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Theis and Singer (33) proposed that organic matter could affect chemical Fe(II) oxidation rates by binding to free Fe(II). Depending on the stability constant of the Fe(II)-organic matter complex (33), the concentrations of organic matter, O 2 , and Fe(II) (19), and the nature of the organic matter (24,30,33), organic matter can either inhibit, accelerate, or have no effect on abiotic Fe(II) oxidation. For example, the inhibition of chemical oxidation rates by bacterial exopolysaccharides was also proposed as a mechanism to explain higher rates of Fe plaque (oxide) formation on axenic rice (Oryza sativa) roots than on nonaxenic rice roots (18).…”
Section: Contribution Of Bacterial Metabolism To Fe(ii) Oxidationmentioning
confidence: 99%
“…Theis and Singer (33) proposed that organic matter could affect chemical Fe(II) oxidation rates by binding to free Fe(II). Depending on the stability constant of the Fe(II)-organic matter complex (33), the concentrations of organic matter, O 2 , and Fe(II) (19), and the nature of the organic matter (24,30,33), organic matter can either inhibit, accelerate, or have no effect on abiotic Fe(II) oxidation. For example, the inhibition of chemical oxidation rates by bacterial exopolysaccharides was also proposed as a mechanism to explain higher rates of Fe plaque (oxide) formation on axenic rice (Oryza sativa) roots than on nonaxenic rice roots (18).…”
Section: Contribution Of Bacterial Metabolism To Fe(ii) Oxidationmentioning
confidence: 99%
“…Therefore, association of LPS with metals, although an experimental nuisance, is likely to be the biological norm, as some liberation of metals is a likely consequence of tissue necrosis at the site of infection. Some authors have suggested that LPS may serve as a metal‐binding substance for Gram‐negative bacteria, in the microbe versus host struggle for biologically important metal ions (Roth et al ., 2000). Although studies of the strength of LPS–metal binding interactions suggest that endotoxin would be a poor competitor for metals with most host metal‐sequestering proteins (Šourek and Tichý, 1975), it may nevertheless represent an effective scavenger of ‘free’ metal ions.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies of the strength of LPS–metal binding interactions suggest that endotoxin would be a poor competitor for metals with most host metal‐sequestering proteins (Šourek and Tichý, 1975), it may nevertheless represent an effective scavenger of ‘free’ metal ions. Furthermore, there is preliminary evidence to show that interactions between LPS and metals may have pathological relevance, as LPS is known to speed the oxidation of ferrous iron, and may thus aggravate damage due to oxidative stress (Roth et al ., 2000). Other studies have shown synergistic interactions between LPS and metals in induction of cytokine production by mammalian immune cells (Scuderi, 1990).…”
Section: Discussionmentioning
confidence: 99%